Cost-effectiveness of the Floodlight MS app in Austria. Unlocking the mystery of costs and outcomes of a digital health application for patients with multiple sclerosis - Evelyn Walter; Matthäus Traunfellner; Franz Meyer; Christian Enzinger; Michael Guger; Christian Bsteh; Patrick Altmann; Harald Hegen; Christoph Goger; Veronika Mikl (Digital Health)
Objective Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease affecting 2.9 million people worldwide, often leading to permanent disability. MS patients frequently use eHealth tools due to their relatively young age. The Floodlight ® MS app is a scientifically designed smartphone application that helps patients monitor hand motor skills, walking ability and cognition between medical appointments. This study assesses the cost-effectiveness of using the Floodlight ® MS app alongside standard-of-care (SoC) versus SoC alone in patients with relapsing-remitting MS (RRMS) from the perspective of the healthcare system. Methods A 10-year decision-analytic model was developed to assess the cost-effectiveness of incorporating the Floodlight ® MS app alongside SoC. The analysis included treatment-naive individuals and those already on drug therapy, modelling the app's role in early detection of disease progression and relapses to improve quality-of-life. Results For treatment-naive patients, using the Floodlight ® MS app resulted in a 2,660 € increase in total costs but yielded potential medical-cost savings of 786 € through health improvements. These patients experienced fewer relapses and slower disability progression, translating to a quality-of-life improvement of 4.5 months in perfect health and an incremental-cost-effectiveness-ratio (ICER) of 7,071 €. Pre-treated patients showed similar trends, with medical-cost savings of 718 €, an ICER of 7,864 €, and a quality-of-life improvement of 4.2 months. Higher effectiveness (+5%) led to an additional 8.3 months in perfect health and a reduction in overall costs. Conclusion The analysis demonstrates that the Floodlight ® MS app is a cost-effective digital health application, encouraging broader discussions on maximizing the potential of software-as-medical-devices within the care pathway.